The Neolithic in Arabia: a view from the south. (18th April 2013) - McCorriston, Joy
Abstract : Maurizio Tosi alerted prehistorians to the significant evidence that Arabia followed its own path and with Serge Cleuziou has made a compelling argument about the distinctive social structure of Arabian complexity. After a decade of research and analyses based in Wadi Sana, Hadramawt, the RASA Project can offer a hypothetical scheme of the earliest social developments in highland southern Arabia. Domesticated animals came first; They were probably adopted or used by hunters still prizing wild game; Dedicated pastoralism emerged in situ, accompanied by an increase in population density and the definition of strategic territories; In southern Arabia, a distinct Neolithic culture of sacrifice began as social‐boundary maintenance to secure resources; Social strategies changed, with the introduction of more complex and broadly negotiated axes of power; Agriculture was introduced late, and the first deliberate cultivation may not have involved domesticated plants. Whatever was cultivated was used to maintain Neolithic populations committed to territories; This Neolithic culture set the foundation for subsequent Arabian cultures.